Description of a new toad of Megophrys Kuhl & Van Hasselt, 1822 (Amphibia: Anura: Megophryidae) from western Yunnan Province, China - Shi, Shengchao; Li, Donghui; Zhu, Wenbo; Jiang, Wen; Jiang, Jianping; Wang, Bin (Zootaxa, 2021)
A new species of genus Megophrys from Gaoligong Mountains, Yunnan Province, China is described. Phylogenetic analyses based on mitochondrial DNA and nuclear DNA all clustered the new species as an independent clade nested into the subgenus Panophrys. The smallest genetic distance based on 16S rRNA gene between the new species and its congeners was 3.0%. The new species could be identified from its congeners by a combination of following characters: moderate body size (SVL 31.0–34.8 mm in males); vomerine ridge weak, vomerine teeth absent; dorsal skin relatively smooth; tongue slightly notched behind; tympanum rounded and relatively large, 0.54 times of eye length; a horn-like tubercle on edge of each upper eyelid small; tibio-tarsal articulation reaches middle eye when leg stretched forward; finger tips rounded, not expanded to small pad; toes with narrow fringes and rudimentary webbing; ventral hindlimbs semitransparent purplish with greyish white pigments; ventral body scattered with distinct dark patches in the middle.